Using the Magnetic Resonance Imaging in Medicine - Kafash, Hiba Mohammed Jabr; Said, Zahraa Mazin MOhammed; Habib, Murtada Saheb Shaker; Shahd, Rusul Tarkhan (American Journal of Botany and Bioengineering, 2024)
This field causes the hydrogen atoms to become magnetized and all of them move toward their northern magnetic side, uniting in one direction. After that, the body is exposed to radio rays that increase the energy of these atoms, and therefore they will change their direction to a certain degree, leaving us with one atom out of every million atoms used in the MRI process. This is a large number of atoms sufficient to produce a clear image of the part to be imaged, and they emit the opposite amount of energy. This reverse energy is received from the device, calculated, and formed in the form of an image. This image shows the intensity of hydrogen in each area of the body, and through this image, doctors are able to detect many diseases.When atoms in the body are excited, the protons move with and against the direction of the main magnetic field. The protons corresponding to the main direction increase by a small amount compared to the antiprotons, but they are very important in obtaining the image later. These protons are especially excited by radio waves and change their position from vertical to horizontal, but they soon become It returns to the equilibrium position, but to return to the equilibrium position Balance There are two important timings.